Use of mobile phone among fisherman for marketing and weather information - Chhachhar, Abdul Razaque; Omar, Siti Zobidah (Societe de Physique et d'Histoire Naturelle de Geneve, 2012)
This article assesses that how the mobile phone has improved the life of fishermen and increased their income. Basis on the literature review it was indicated that how mobile phone has provided an access to fishermen for sell their produce in market. Mobile phone has given a ground to fishermen for communicate with dealer at port and deal for get good price of their catches. Similarly fishermen get latest information about weather before going to sea. By use of mobile phone fishermen have save their time and also their income. Mobile phone has also reduce the gap between rural and urban communities nowadays fishermen directly sell their produce in market without dealing with local brokers. Mobile phones provide fishermen option to take processes to reduce the risks. Especially in case of emergencies when fishermen were in sea.